ANALYSIS OF THE INFLUENCE OF EXPORTS, FOREIGN DEBT, AND REMITTANCES FROM INDONESIAN WORKERS ON FOREIGN EXCHANGE RESERVES IN INDONESIA 2010-2023 - Safitri, Pipin Dwi; Ayu, Putri (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
This study aims to analyze the effect of exports, foreign debt, and TKI remittances on Indonesia's foreign exchange reserves. The method used is the Error Correction Model. The type of data used is secondary, which is a time series with a quarterly period from 2010 to 2023 obtained from the Statistik Ekonomi dan Keuangan Bank Indonesia (SEKI BI), the International Monetary Fund (IMF), and the Central Statistics Agency (BPS). The results show that in the long term, partially exports and foreign debt are positive and significant to Indonesia's foreign exchange reserves, while TKI remittances are not significant. In the short term only foreign debt is significant but negative, the rest of the changes in foreign debt and TKI remittances do not significantly affect foreign exchange reserves.